Aggregate Planning Analysis in PT. Akebono Brake Astra Indonesia - Fajar, Mohammad; Lestari, Yuliani Dwi (Journal of Business and Management, 2017)
AbstractNowadays, most manufacturing companies are striving for greater profit and improvement to gain competitive advantage towards others. Such profit can be achieved by making more income or attenuate production expenses. In order to do so, manufacturers has been developing various kinds of production system in order tomaximize inventory utilization, production forecast, and production planning. Therefore,by applying certain operations management decision might lead to better result of production and inventory planning. Manufacturers around the world have been using combinations of aggregate planning models in any ways imagined to achieve best results in terms of production effectivity and cost, especially in automotive manufacturing industries which requires high planning precision with a lean inventory. PT. AAIJ is an automotive parts manufacturing company which supplies to both national and international market. PT. AAIJ however, they had been facing production shortage to its biggest client to the company, Nissan Motor UK Products since September to December 2016. Based on an ABC analysis, production shortage analysis has been focused only on Nissan Motor UK Products.Keywords: Holding, Inventory Management, Inventory, MPS, MRP, Operations Management, Overstock, Production Management System, Production Planning, Shortage.